Interrater Reliability of the Icelandic Translation of the DSM-5 Version of the Schedule for Affective Disorders and Schizophrenia for School-Age Children – Present and Lifetime Version (K-SADS-PL) - Hans Hektor Hannesson 1994- (2023)
Background: The Schedule for Affective Disorders and Schizophrenia for School-Age Children-Present and Lifetime version (K-SADS-PL) is a semi-structured interview and a widely used diagnostic tool for psychological disorders in children and adolescents. The interrater reliability of K-SADS-PL has been researched to some extent, but studies often lack information on individual disorders and provide fragmentary information on the interrater reliability of K-SADS-PL. Objectives: This study will re-examine the interrater reliability of the Icelandic translation of K-SADS-PL, expanding on established research and gaining more insight into less common disorders that have not been explored sufficiently, furthering our understanding of the interrater reliability of K-SADS-PL. Method: K-SADS-PL was administered to a clinical sample of outpatients from two locations: The Icelandic Anxiety Centre for Children, Adolescents, and Young Adults, and The Department of Child and Adolescent Psychiatry at the Landspítali University Hospital in Reykjavík, Iceland. Results: The Dataset included 135 patients aged 6-18 who agreed to participate in the study. Interrater reliability was assessed using Cohen’s κ, with results ranging from poor to excellent (0.3-1.0) but most disorders showed excellent reliability (κ>0.75). Discussion: These results show that the Icelandic translation of the DSM-5 K-SADS-PL is generally reliable when administered by adequately trained post-graduate students, with most disorders demonstrating fair to excellent reliability.